Análise da qualidade da água para reaproveitamento em uma obra de captação de água subterrânea na cidade de Angicos/RN - Pereira, Mylliane Samara Soares (Universidade Federal Rural do Semi-Árido, 2019)
The reality of the municipality of Angicos is similar to that of others in the northeastern semi-arid region, characterized by long periods of drought and short rainy seasons. Thus, it is necessary that the management of water resources has an optimization in order to meet the needs of the region. The population growth associated with water use levels shows excessive consumption, waste and contamination, generating public health problems, as it directly affects its quality. Water potability issues are governed in the country by Ordinance 2.914 / 2011 / MS. From this perspective, a study of the physicochemical parameters was carried out with samples of water distributed in the municipality, coming from an artesian well, in order to verify the quality of water consumed by the population, the waste water, and to suggest methods of reuse. As for the analyzes performed, there was variation in some parameters, which prevented the waste water from being reused. In short it can be said that the water offered to the residents of the municipality is characterized as potable. It can be said that the municipality offers quality water to its residents through the well under study and wasted water has a very high hardness index, which makes its use impossible at the moment. For such procedure, a case study of an applied nature was carried out, with the objective considered exploratory and quantitative approach.
Keywords: Potabilidade da água; Consumo de água; Poço artesiano; Parâmetros físico-químicos; Water potability; Water consumption; Artesian well; Physical and chemical parameters; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA